ANALYSIS OF THE NUMERACY SKILLS OF JUNIOR HIGH SCHOOL STUDENTS IN SOLVING SYSTEMS OF LINEAR EQUATIONS WITH TWO VARIABLES (SPLDV) PROBLEMS - Rahim, Essy Puspita; Maimunah, Maimunah; Suanto, Elfis (Jurnal Pendidikan Matematika dan IPA, 2025)
This research is motivated by the fact that numeracy skills are fundamental abilities that every student must possess. However, observations in the field indicate that students' mathematical abilities, particularly in the topic of systems of linear equations with two variables (SPLDV), are still relatively low. This study aims to describe students' numeracy skills, which are divided into three stages: (1) knowing, (2) applying, and (3) reasoning. The study involves 20 eighth-grade students as subjects. The method used is descriptive qualitative, with data collection techniques including tests, interviews, and documentation. Data analysis is conducted based on three levels of numeracy skills: high, medium, and low. The results show that students' computational abilities in the SPLDV material are generally low, with an average score of 33%. The implications of these findings highlight the need for the implementation of more varied and contextual teaching strategies to enhance students' computational skills. This research can serve as a foundation for teachers to provide further assistance to students facing difficulties, with an emphasis on improving overall computational abilities.